2019
DOI: 10.1021/acs.langmuir.9b01040
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction of Anisotropic Superhydrophobic Surfaces Prepared by Laser Etching

Abstract: In this research, the anisotropic superhydrophobic surface is prepared on a stainless steel surface by laser etching, and the drag reduction property of the anisotropic surface is studied by a self-designed solid−liquid interface friction test device. Periodic arrangement structures of quadrate scales with oblique grooves are obtained on a stainless steel surface by a laser. After modification by fluoride, the surface shows superhydrophobicity and anisotropic adhesive property. Here, the inclined direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…The WCA can be as large as 153.6 • after modification with stearic acid. Tuo et al developed an anisotropic superhydrophobic surface on a stainless steel surface by laser etching [32]. They used an ultraviolet laser to etch the steel by rotating the substrate to different angles.…”
Section: Etching Methodsmentioning
confidence: 99%
“…The WCA can be as large as 153.6 • after modification with stearic acid. Tuo et al developed an anisotropic superhydrophobic surface on a stainless steel surface by laser etching [32]. They used an ultraviolet laser to etch the steel by rotating the substrate to different angles.…”
Section: Etching Methodsmentioning
confidence: 99%
“…After this, as turbulent boundary layer flows representing the main applications, the possibility of superhydrophobic surface drag reduction in turbulent flow turned into the next concern [98][99][100]. In 2009, Daniello et al [7] confirmed the feasibility of superhydrophobic surfaces in turbulent drag reduction, and a drag reduction approaching 50% was measured.…”
Section: Drag Reduction By Superhydrophobic Surfacesmentioning
confidence: 99%
“…This is because of the creation of microbubbles between substrate and water flow that leads to water slippery over the surface and thus more reduction in drag. Tuo et al [32] fabricated anisotropic SHS on stainless steel comprising inclined grooves by laser etching and fluoride treating for drag test. Comparing inclined and reversed direction of ribs, while drag-drop ratio in the first situation is about 18%, it is almost 48% in the latter under 4.48m/s flow velocity.…”
Section: Literature Reviewmentioning
confidence: 99%